(untitled) (Progressive Agriculture, 2014)
The study was carried out to determine the extent of training needs of the fish farmers on integrated fish farming and to explore the relationship between the selected characteristics of the fish farmers and their extent of training needs on integrated fish farming (IFF). Four villages, namely North Gouari, South Gouari, Rajpur and Satrasia under Muktagacha Upazila (sub-district) of Mymensingh district were the locale of the study. Ninety fish farmers (out of the total of 300) were randomly selected as a sample of the study. Data were collected from the sample of fish farmers by using a pre-tested interview schedule through personal interview method during 15 to 30 April 2013. Pearsons Product Moment Correlation Coefficient (r) was computed to explore the relationships between the selected characteristics of the respondents and their extent of training needs on IFF. Training needs of the fish farmers on IFF was the dependent variable and selected characteristics of the respondents constituted the independent variables of the study. The highest proportion (56.7 per cent) of the respondents had high training needs while 42.2 per cent of the respondents had medium and only 1.1 per cent had low training need on IFF. The training needs for selection of diseases free seed and species ranked first followed by training needs for ways of diseases control. Sequentially training needs for breed selection was third, training needs for stocking density of fish species was fourth training needs for preventive measures of diseases was fifth and training need for techniques of egg collection was last in the rank order. Correlation analyses indicated that five characteristics of the integrated fish farmers, namely years of schooling, organizational participation, communication exposure, social mobility and knowledge with IFF had significant positive relationships with their extent of training needs on IFF. The household size, age and annual income showed no significant relationships with their extent of training needs on IFF and showed negative trend. The main problems on IFF were unavailability of quality seed and species, lack of financial support, lack of knowledge on species selection, lack of marketing facilities, lack of knowledge on fish processing and preservation. The extension service providers should arrange more training and motivational campaign for the fish farmers on IFF. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19171 Progress. Agric. 24(1&2): 181 - 189, 2013